Dzietność rodzin. Stan aktualny i perspektywy - Smoliński, Zbigniew (Wydział Prawa i Administracji UAM, 1981)
In the years 1900 -1970 transition occured from natural to rational fertility, and from great to small number of children in families (women). The total fertility coefficient declined from 6,230 in the years 1900/1901 to 2,244 in 1968. In last 12 years it remained at the level 2,200 - 2,300. It means also stabilization of the number of children in married couples. This fact indicates the timeliness of the results of specific research on fertility of married couples, in marriages concluded in latest several years, which were carried out by the Central Statástical Office in the years 1972 and 1977. In the relatively short marriage state longitude (0 - 10 years) realized number of children is only 1.0 child when the marriage lasts 0-4 years and 1.9 child for 5 - 9 years. On the other hand, the number declared for realization in the next years is 1.2 and 0.4 respectively. It means that the total fertility among young couples is realized at the level of 2.2 - 2.3 children what corresponds with minimally enlarged population's reproduction. This fertility settles itself between the planned number of children at the beginning of the marriage (2.1) and ideal number of children in the moment of examination (2.6). There occurs uniformization of a family model, that in 75 per cent is composed of two or three children, in relation 2 : 1 . These magnitudes (while the number of children more than three prevails the less than two children' number) ensure at least a simple Poland's population reproduction in the next years.
Number of Children in Families. Present Situation and Perspectives